2021
DOI: 10.3390/nu13082867
|View full text |Cite
|
Sign up to set email alerts
|

The Double Burden of Malnutrition and Associated Factors among South Asian Adolescents: Findings from the Global School-Based Student Health Survey

Abstract: The health and nutrition of the global adolescent population have been under-researched, in spite of its significant size (1.2 billion). This study investigates the prevalence and associated factors of malnutrition (stunting, thinness and overweight) among adolescents living in South Asia. The sample analysed was 24,053 South Asian schooled adolescents aged 12–15 years that participated in the cross-sectional Global School-Based Student Health Survey (GSHS) between 2009 and 2016. The prevalence of stunting, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 68 publications
1
0
0
1
Order By: Relevance
“…In Bangladesh, the rate of stunted children is considered to be higher than the rate of underweight and wasted problems due to the high incidence of childhood infections, and maternal anxiety during pregnancy. A similar finding is revealed in previous research (Ahmed et al, 2021;Dewey & Begum, 2011;WHO, 2021) and a previous study showed the reverse findings (Querol et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In Bangladesh, the rate of stunted children is considered to be higher than the rate of underweight and wasted problems due to the high incidence of childhood infections, and maternal anxiety during pregnancy. A similar finding is revealed in previous research (Ahmed et al, 2021;Dewey & Begum, 2011;WHO, 2021) and a previous study showed the reverse findings (Querol et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…(valor de p= 0.4). (Estecha et al, 2021) La duración del sueño en los adolescentes y el desarrollo de la obesidad y el sobrepeso, no tienen una relación estadísticamente significativa en este estudio (OR = 1,0; valor p= 0.96), sin embargo, en un estudio observacional, de cohorte retrospectivo, realizado por Barajas Herrera y otros Ciencia Latina Revista Científica Multidisciplinar, Ciudad de México, México. ISN 2707-2207/ISSN 2707-2215 (en línea), enero-febrero, 2023, Volumen 7, Número 1 p 4203 los pediatras de la Red Centinela Sanitaria en el año 2018 en España, se encontró que la duración del sueño y la prevalencia de exceso de peso en los adolescentes se encuentran directamente relacionados.…”
Section: Característicasunclassified